Urban Poverty and civic Tradition of Acceptance - Ilaria Agostini (In_Bo, 2018)
Cities are haunted by people living without any form of civil rights, welfare, health, social relations: homeless, nomads, “illegal” immigrants, walkers and wanderers, refugees and stateless, beggars, amputees in wars having place far from the safe Europe. Their existence generates mistrust and suspicion on one hand, challenging on the other the civil conscience of the contemporary society. It is a sort of memento mori: an incumbent mourning for the possible loss of citizen status. The historic city has proved capable of hosting marginalisation and deviance, through institutions or architectural devices. Does the neoliberal city, generating social inequalities and managed in the name of security, still has room for such unsettled and unsettling presences? Can it treat them only as “waste” or, vice versa, grant them the dignity of a different dwelling within a universal coexistence?